(untitled) (Coffee Science - ISSN 1984-3909, 2014)
Evaluation systems of soil cover in coffee field associated with grevilleas - The aim of this study was conduct a comparative analysis between two systems for the evaluation of coffee trees associated with grevileas arranged in densities between 31 to 277 grevileas. The evaluations were based in adaptation of point interceptation transect with denomination of “Tip shoes” and by traditional image analyses by a Siscob Embrapa software. Soil covering, bare soil, green vegetation and tillage percentage was evaluated and defined regression equations in function to tree densities. The values discrepancy verified between two methods were related to differences in basis of fundamental conception, being justified the specificity to best adjustment to utilization of each evaluating system.